The Management of Industrial Safety in Chemical and Petrochemical Industry by Comparing Costs and Benefits - Chiara Vianello; Francesca Milazzo Maria; Giuseppe Maschio (Chemical Engineering Transactions, 2018)
Chemical and petrochemical installations are complex installations, thus, for these huge efforts are needed to protect people/workers and the environment from the occurrence of major accidents. Due to this evidence, an increased attention has been paid by designers and operators in finding innovative solutions to guarantee higher levels of safety, in order to avoid that failures and losses of containment from process equipment could lead to serious consequences. To this purpose, the RBI approach is usually used to identify critical equipment where inspections will provide the highest benefit in reducing the overall risk. The application of this methodology permits a significantly reduction of maintenance costs and simultaneously the increase of plant's reliability and availability. It must be added that, in order to increase safety, also a proper selection of measures to be adopted is needed. In this work, the RBI method has been applied, by means of a recent developed tool named Inspection Manager, to support the selection of measures to be adopted with respect to an accidental event causing the release of hazardous materials.